Strategi Penerapan SOP Pramusaji di Tijili Hotel Seminyak - Ni Kadek Ayu Intan Sari; I Gusti Ayu Melistyari Dewi; Kadek Feni Aryati (Abdimas Indonesian Journal, 2026)
The purpose of this community service is to optimize waiter service at Tijili Hotel Seminyak, as well as to overcome obstacles and elements that support the process. This study uses a descriptive qualitative approach and collects data through participant observation, in-depth interviews with waiters, supervisors, managers, and documentation investigations. The results of interviews, documentation and observations indicate that there is a high workload during peak hours and this condition creates a significant difference between the number of available workers and the amount of work that has just been completed, the lack of understanding and mastery of procedures in new waiters which makes mastery of all service procedures incomplete and in-depth so that problems often arise that hinder service and disrupt the uniformity of work standards and the existence of communication and coordination between staff that is not optimal is the main cause of service errors, delays, and guest discomfort, especially in the midst of busy dining rooms. Based on these findings, this community service was carried out to find solutions to these problems in the form of providing training, conducting daily briefings and arranging a more flexible work schedule.To address this issue, a real-world needs-based work system was created. This allows for workload balance, improving the quality of human resources so that all employees have equal skills, and organizing the flow of information to ensure everyone can communicate effectively with each other. The implementation of this solution has demonstrated significant improvements; service has become smoother, more standardized, and more consistent, errors have been significantly reduced, and the work environment has become more cohesive and focused on guest satisfaction.